Clinical and laboratory indicators as determinants of a pattern in the evolution of serious oral infections - A 3-year retrospective study (Research, Society and Development, 2022)
Objective: To evaluate possible clinical and laboratory indicators that could determine a pattern in the evolution of infections and guide professionals to take a better approach, avoiding further complications and bad results. Material and Methods: Data from 440 patients were collected during 3 years at Hospital Alípio Corrêa Netto. The data collection period was from July 2018 to July 2021. We analyzed whether the presence of underlying diseases, trismus, oral spaces and whether or not changes in laboratory tests could determine a pattern in the course of treatment of infections. Results: Mean age was 26.5 years. The main signs and symptoms were: Pain, Prostration, Trismus, Fever, Odynophagia and dyspnea. In 65% of cases, multiple spaces were involved in the infection. The underlying disease showed greater statistical significance. Patients with underlying disease needed to be treated with general anesthesia due to the greater degree of severity. The mean length of hospital stay was 8.1 days for systemically compromised patients versus 4.2 for healthy patients. The CRP value was strongly influenced by the underlying disease, with an average of 45 mg/L for compromised patients versus less than 20 mg/L for healthy patients. Conclusion: Systemic patients should be treated with greater attention, because they tend to have higher trismus, CRP values, need for treatment in the operating room and length of stay, especially in the ICU, which demonstrates a greater severity of cases.